Comment on "Detrital Zircons From the Nanaimo Basin, Vancouver Island, British Columbia: An Independent Test of Late Cretaceous to Cenozoic Northward Translation" by Matthews et al. Issue 10 (3rd October 2018) - Haggart, James W.; Mahoney, J. Brian; Ward, Peter D.
Key Point: Errors in stratigraphic age assignment of Cretaceous detrital zircon samples result in incorrect understanding of ages of geologic units